HIGH-FREQUENCY CHEST WALL OSCILLATION: AIRWAY CLEARANCE MANAGEMENT FOR OBSTRUCTIVE PULMONARY DISEASE PATIENTS - Angelika Quissesa; Juhdeliena Juhdeliena; Eva Chris Veronika Gultom (Universitas Pelita Harapan, 2021)
Ineffective mucous airway clearance is identified as the main concern in obstructive pulmonary disease. An impaired mucociliary mechanism and hyper secretive are leading to mucous retention. High-frequency chest wall oscillation (HFCWO) offers a great practical advantage for obstructive pulmonary disease treatment. A literature review was conducted to summarize the existing research evidence assessing the effectiveness and benefits of HFCWO as an airway clearance management among people with obstructive pulmonary disease. Literature was limited to accessible articles in the English language and sourced from electronic databases, PubMed and EBSCO, from their published date through 2010. Seven studies that fulfilled the inclusion criteria were included in the analysis. Two themes were identified from the summary of included studies, namely respiratory function improvement and quality of life outcomes. The overall results of the studies indicate that HFCWO positively affects health status and wellbeing in patients with excessive mucous production and impaired airway clearance mechanism. It also can be performed independently and enhances self-satisfaction. Thus, it will be advantageous to include the HFCWO in pulmonary rehabilitation. Further studies are needed to validate the effectiveness of HFCWO in obstructive pulmonary disease patients and develop better treatments in this field.